Exposing pay : pay transparency and what it means for employees, employers, and public policy - Bamberger, Peter (Ascent Audio, 2023)
Pay equity has become a hot topic in recent years with pay transparency viewed as an important way to narrow gender and racial pay gaps. However, pay transparency policies and practices remain highly controversial, with divergent attitudes based largely on conjecture or anecdote. In Exposing Pay, Peter Bamberger provides evidence-based insights into how pay communication policies and practices impact outcomes at individual, organizational, and societal levels. Bamberger reviews findings from the recent surge in pay transparency research to help employees, managers, and policymakers better understand when pay communication policies and practices might enhance organizational performance and address social inequality and when such practices can lead to harmful consequences. Starting with a short overview of how companies have addressed the question of pay transparency over the past century and a brief summary of contemporary transparency regulations in dozens of countries around the world, Exposing Pay presents findings on the various forms of pay transparency on such outcomes as individual task performance, employee retention and turnover, citizenship behaviors such as helping, counter-productive work behavior, and pay dispersion or spread.